Elucidating novel disease mechanisms in severe asthma - Kim,RY; Rae,B; Neal,R; Donovan,C; Pinkerton,J; Balachandran,L; Starkey,MR; Knight,DA; Horvat,JC; Hansbro,PM (Clinical & Translational Immunology, 2016)
Corticosteroids are broadly active and potent antiinflammatory agents that, despite the introduction of biologics, remain as the mainstay therapy for many chronic inflammatory diseases, including inflammatory bowel diseases, nephrotic syndrome, rheumatoid arthritis, chronic obstructive pulmonary disease and asthma. Significantly, there are cohorts of these patients with poor sensitivity to steroid treatment even with high doses, which can lead to many iatrogenic side effects. The doselimiting toxicity of corticosteroids, and the lack of effective therapeutic alternatives, leads to substantial excess morbidity and healthcare expenditure. We have developed novel murine models of respiratory infectioninduced, severe, steroidresistant asthma that recapitulate the hallmark features of the human disease. These models can be used to elucidate novel disease mechanisms and identify new therapeutic targets in severe asthma. Hypothesisdriven studies can elucidate the roles of specific factors and pathways. Alternatively, 'Omics approaches can be used to rapidly generate new targets. Similar approaches can be used in other diseases.